Marc Nagtzaam : reissue - Nagtzaam, Marc; Sharp, Chris; Roelstraete, Dieter (Amsterdam : Roma Publications, ©2011.)
Nagtzaam's meticulous graphite-gray pencil drawings are often abstract, geometric but also seek to be representations of a concrete reality or space. His drawings take up the entire page and appear almost impenetrable. After a series of artist publications this book is the first monograph with a broad selection of his work from 1995 to today.
boek